Oris in pomen postopka kolektivnih pritožb po Evropski socialni listini – skrajni čas za njegovo pogostejšo uporabo? - Polajžar, Aljoša (Delavci in delodajalci, 2021)
The author discusses the system of collective complaints in the context of the protection of economic and social rights under the European Social Charter. The author concludes that the role of international and national representative organisations of workers and employers is particularly important in the context of the collective complaints procedure system, given the limited scope of eligible applicants. In this light, the aim of the paper is to shed light on the legal issues of the collective complaints procedure, and thus encourage the social partners to use it more frequently.
Keywords: European Committee of Social Rights; European Social Charter; Evropska socialna listina; Evropski odbor za socialne pravice; representative trade unions; reprezentativni sindikati; sistem kolektivnih pritožb; the collective complaints procedure; the protection of labour rights; varstvo delavskih pravic